2022
DOI: 10.3390/ijerph19095674
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Outpatient Visits for All-Cause and Chronic Diseases in Korea: A Nationwide Population-Based Study

Abstract: This study explores the impact of the coronavirus disease 2019 (COVID-19) pandemic on outpatient visits for all-cause and chronic diseases in 2020. We extracted the data of patients who visited medical institutions over the past five years (2016–2020) from nationwide claims data and measured the number of monthly outpatient visits. A negative binomial regression model was fitted to monthly outpatient visits from 2016 to 2019 to estimate the numbers of 2020. The number of all-cause outpatient visits in 2020 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The pandemic has challenged public health systems worldwide, revealing that even seemingly robust health systems can be rapidly overwhelmed and compromised ( 3 6 ). Health seeking behavior for routine care also declined during the COVID-19 pandemic ( 7 10 ). In the US, for example, the combination of increased workload and reduced number of health workers due to infection, fears about exposure, and burn-out, led to a severe strain on the capacity to maintain essential services ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has challenged public health systems worldwide, revealing that even seemingly robust health systems can be rapidly overwhelmed and compromised ( 3 6 ). Health seeking behavior for routine care also declined during the COVID-19 pandemic ( 7 10 ). In the US, for example, the combination of increased workload and reduced number of health workers due to infection, fears about exposure, and burn-out, led to a severe strain on the capacity to maintain essential services ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with reports across the World, a study conducted in Japan demonstrated a decrease in outpatient clinic prescriptions, with drugs for respiratory diseases most affected and antineoplastic least affected 41 , it correlates with other studies carried out in Japan that revealed a temporary decline in physician visit by patients with chronic conditions 42 . A study carried out in Korea reported a decline in outpatient visits for all cause and chronic diseases than was expected in 2020 43 , in this study there were discrepancies in clinic attendance amongst patients with different chronic diseases, the decline in outpatient visits were more pronounced in these with respiratory, neurological and liver diseases (11.5%,7.1% and 6.2%) respectively, it was less with diabetes, malignant neoplasm , heart disease, thyroid conditions and mental and behavioral disorders 43 . Several studies across Korea reported that the delay in seeking or avoid seeking care was for the fear of being infected by COVID-19 44,45 , this perceived risk fluctuated depending on the pandemic wave 46 .…”
Section: Impact On Health Care Settingsmentioning
confidence: 89%
“…Research from the perspective of healthcare service supply also shows that relatively low-priority healthcare services for non-COVID-19 patients were postponed or canceled due to the surge in COVID-19 [ 41 ]. However, Korea may have experienced minimal impact in this regard because its healthcare system was not overwhelmed by the COVID-19 pandemic [ 42 ]. Nevertheless, the interval between outpatient visits may have increased because of changes in doctors’ practice.…”
Section: Discussionmentioning
confidence: 99%